Pendekatan Pembelajaran Mendalam sebagai Upaya Pengembangan Kecerdasan Logis dalam Matematika Sekolah Dasar - Nurhaswinda Nurhaswinda (Jurnal Pendidikan, Kepelatihan, Olahraga, dan Kesehatan, 2025)
The deep learning approach in education has become an important strategy for developing students' logical intelligence, particularly in mathematics learning in elementary schools. Logical-mathematical intelligence is the ability to think analytically, systematically, and critically, which is essential for solving mathematical problems. This literature review aims to analyze the concept, implementation, and impact of the deep learning approach on the development of logical intelligence in elementary school students. The research method used a literature study approach by collecting and reviewing scientific articles, journals, and books related to deep learning, logical intelligence, and mathematics education. The review results indicate that the deep learning approach can improve students' analytical skills, logical reasoning, and mathematical creativity through problem-based learning strategies, projects, and active exploration of mathematical concepts. In addition, the use of digital technology and interactive media in deep learning can facilitate the understanding of abstract concepts and increase student engagement. Learning that emphasizes reflection, discussion, and collaboration has also proven effective in developing logical intelligence. However, implementation requires teacher readiness, infrastructure support, and appropriate curriculum adaptation. This study concludes that the deep learning approach is a potential strategy for developing logical intelligence in elementary school mathematics education, with recommendations for further research exploring specific learning models and evaluating their impact on student achievement.